The Surface Energy Balance of a Himalayan Mature Pine (Pinus roxburghii) Ecosystem During Drought Stress Conditions - Sandipan Mukherjee; Priyanka Lohani; Krishna K. Osuri; Rajiv Pandey; A. P. Dimri (Meteorological Applications)
ABSTRACT This study presents the energy balance dynamics of a mature Pine (Pinus roxburghii) ecosystem of the Indian Himalaya using multiple year (March 2020 to December 2022) eddy covariance‐based measurements. Efforts are made to quantify the inter‐annual dynamics of surface energy balance at seasonal and annual time scales. The impact of drought conditions, induced by soil moisture and vapor pressure deficit, on energy partitioning of the ecosystem is quantified using Bowen ratio (β) and evaporative fraction (EF). The energy balance closure is assessed for three seasons (i.e., pre‐monsoon, monsoon, and post‐monsoon) of each observation year. We find that the closure fraction (CF) of the site is more than 80% on an annual scale. Higher CF is observed during pre‐monsoon (⁓80%) and monsoon (⁓90%) seasons due to the onset and duration of the growing season. The available energy partitioned into latent heat flux is larger than the sensible heat flux for the ecosystem, signifying that evapotranspiration is one of the dominant components of water and energy budgets. The evaporative cooling at the site takes place during the monsoon season through higher EF; however, the Pine ecosystems sustained the dry pre‐monsoon season with higher β values. We find that the soil moisture‐induced drought at the site resulted in higher partitioning of the available energy to sensible heat flux, effectively promoting the drought stress condition. However, it is to be noted that a better comprehension could be made for Pine forest behavior under environmental stress if such studies are further replicated.